A Comparison of Characterization and Moral Values in Cinderella and Bawang Merah Dan Bawang Putih Fairy Tales: A Comparative Literature Study - Sijabat, Asnita br (International Journal of Education, Information Technology, and Others, 2023)
In this research, the researcher intends to examine the character and moral values in the fairy tales Cinderella and Bawang Merah Bawang Putih as a comparison. Comparison is intended to find similarities and differences in the two fairy tales. The two fairy tales were chosen because the stories have similarities and differences. The two fairy tales can be compared because they have the same theme, namely injustice. This type of research is qualitative descriptive research. Research Target/Subject This research is library research. The research material is two fairy tale literary works entitled "Cinderella," which is the work of the American writer, Marcia Joan Brown in 1954, and "Bawang Merah Bawang Putih" (Collection of fairy tales: 2011), which is one of the fairy tales from Indonesia . The results of this research found similarities and differences in character and moral values in the fairy tales Cinderella and Bawang Merah Bawang Putih. Similarities and differences in the characters of the two fairy tales. In the Cinderella fairy tale, the main character is Ella, a girl who has a beautiful face and noble character. He was always abused by his stepmother and two stepsisters after his father died. Ella lives her life with patience in facing life's twists and turns, until finally she meets a good prince and becomes his wife. Meanwhile, in the fairy tale Bawang Merah Bawang Putih, the main character is Bawang Putih, who was also tortured by her stepmother and Bawang Merah. Even though he was treated unfairly, Bawang Putih lived his life steadfastly. Finally, she also found a royal prince who chose her as his wife.